Comparing effects of tillage treatments performed with animal traction on soil physical properties and soil electrical resistivity: preliminary experimental results - Garcia-Tomillo, Aitor (2017)
Soil Compaction results from compressive forces applied to compressible soil by machinery wheels, combined with tillage operations. Draft animal‐pulled equipment may also cause soil compaction, but a huge gap exists on experimental data to adequately assess their impacts and, actually, animal traction is an option seen with increasing potential to contribute to sustainable agriculture, especially in mountain areas. This study was conducted to assess the impacts on soil compaction of tillage operations with motor tractor and draft animals. In a farm plot (Vale de Frades, NE Portugal) treatments were applied in sub‐plots (30 m x 3 m), consisting in a two way tillage with tractor (T), a pair of cows (C) and a pair of donkeys (D). Undisturbed soil samples (120) were taken before and after operations for bulk density (BD) and saturated hydraulic conductivity (Ks). The relative changes in BD observed after tillage in the 0-0.05 m soil depth increased after operations in all treatments. The increase was higher in the tractor sub-plot (15%) than in those where animal traction was used (8%). Before operation Ks class was rapid and fast in all samples, and after operation this value was reduced to 33% in T, whereas it reached 83% in C. Electrical Resistivity Tomography (ERT) was useful as a tool to identify the alterations caused by tillage operations on soil physical status. These preliminary results confirm the potential of animal traction as an option for mountain agri‐environments, yet it requires much wider research to soundly ground its assets.